Building Employee Performance Through Intellectuality, Commitment and Organizational Dynamics - Barnabas Dowansiba; Ansar Ansar; Roni Herison; Kurniawaty Kurniawaty (Journal Of Social Science (JoSS), 2025)
This research aims to build employee performance through Intellectual Ability, Commitment and Organizational Dynamics at the West Papua Provincial Education Office. This study uses a quantitative approach. The research population is all employees of the West Papua Provincial Education Office totaling 128 people, all of whom were used as research samples, using saturated samples. The research data was obtained from the results of filling out the questionnaire and analyzed using SEM-AMOS. The results of the study show that: 1) intellectual ability, organizational commitment have a positive and significant effect on organizational justice, political skills, and employee performance, 2) organizational justice and political skills have a positive and significant effect on employee performance, 3) intellectual ability and organizational commitment have a positive and significant effect on employee performance through organizational justice and political skills.